The correlation between probiotic use and outcomes of cancer patients treated with immune checkpoint inhibitors - Zhang, Lilong; Jin, Qi; Chai, Dongqi; Kuang, Tianrui; Li, Chunlei; Guan, Yongjun; Liu, Li; Wang, Weixing; Deng, Wenhong (Frontiers in Pharmacology, 2022)
Objective: Immune checkpoint inhibitors (ICIs) have recently demonstrated promising results in improving the prognosis of cancer patients. The goal of this meta-analysis was to determine the impact of probiotic use on the survival of cancer patients treated with ICIs. Methods: Before March 3, 2022, the eligible literature was searched using PubMed, EMBASE, Cochrane Library, Google Scholar, and Clinical trials.gov databases. Overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and disease control rate (DCR) were the primary endpoints. Results: A total of 6 studies met the inclusion criteria, and 1123 patients were included. Meta-analysis showed a trend for probiotic use to prolong PFS (HR: 0.585, 95% CI: 0.328-1.045, P = 0.070) and increase DCR (HR: 1.868, 95% CI: 0.890-3.922, P = 0.099), although it was of borderline statistical significance. We also found that probiotics significantly improved OS (HR: 0.526, 95% CI: 0.341-0.812, P = 0.004) and ORR (OR: 2.831, 95% CI: 1.578-5.076, P < 0.001) in ICI-treated cancer patients. Besides, subgroup analysis showed that non-small cell lung cancer (NSCLC) patients treated with ICIs in combination with probiotics would achieve significantly longer PFS (HR: 0.532, 95% CI: 0.354-0.798, P = 0.002) and OS (HR: 0.528, 95% CI: 0.306-0.912, P = 0.022), as well as higher ORR (OR: 2.552, 95% CI: 1.279-5.091, P = 0.008) and DCR (OR: 2.439, 95% CI: 1.534-3.878, P < 0.001). Sensitivity analysis showed that the above results are stable and reliable. The publication bias test confirmed that there was no publication bias in these results. Conclusion: Current evidence reveals that probiotics can improve the efficacy of ICI treatment in NSCLC patients.